Fear of clowns: An investigation into the aetiology of coulrophobia - Tyson, Philip John; Davies, Shakiela K.; Scorey, Sophie; Greville, William James (Frontiers in Psychology, 2023)
Fear of clowns or coulrophobia is a little understood phenomenon despite studies indicating that it has a high prevalence in the general population. There have been no previous investigations into the aetiology of this fear, although several plausible hypotheses from the wider literature can be generated; the fear stems from media portrayals of scary clowns, from the unusual physical appearance or the unpredictable behaviour displayed, or it derives from an unpleasant personal experience. The current study reviews the literature in this area and also pilots a new questionnaire (Origin of Fear of Clowns Questionnaire; OFCQ) to explore the causes of the fear of clowns in a sample of 528 participants who reported such a fear. Our findings suggest that media influences, unpredictability of behaviour and uncertainty about harmful intent play an important role in the origins of coulrophobia. There are also multiple features of clown appearance which produce a negative experiential state and a sense of a direct threat. We conclude that the origins of clown fear are multifactorial, but seem to prominently involve the influence of the media in addition to the behaviour exhibited and the facial characteristics they display.